Lipoprotein(a) concentration is associated with plasma arachidonic acid in subjects with familial hypercholesterolaemia. Issue 7 (2nd July 2019) - Narverud, Ingunn; Bogsrud, Martin P.; Øyri, Linn K. L.; Ulven, Stine M.; Retterstøl, Kjetil; Ueland, Thor; Mulder, Monique; Roeters van Lennep, Jeanine; Halvorsen, Bente; Aukrust, Pål; Veierød, Marit B.; Holven, Kirsten B.
Abstract: Elevated lipoprotein(a) (Lp(a)) is associated with CVD and is mainly genetically determined. Studies suggest a role of dietary fatty acids (FA) in the regulation of Lp(a); however, no studies have investigated the association between plasma Lp(a) concentration and n -6 FA. We aimed to investigate whether plasma Lp(a) concentration was associated with dietary n -6 FA intake and plasma levels of arachidonic acid (AA) in subjects with familial hypercholesterolaemia (FH). We included FH subjects with ( n 68) and without ( n 77) elevated Lp(a) defined as ≥75 nmol/l and healthy subjects ( n 14). Total FA profile was analysed by GC–flame ionisation detector analysis, and the daily intake of macronutrients (including the sum of n -6 FA: 18 : 2 n -6, 20 : 2 n -6, 20 : 3 n -6 and 20 : 4 n -6) were computed from completed FFQ. FH subjects with elevated Lp(a) had higher plasma levels of AA compared with FH subjects without elevated Lp(a) ( P = 0·03). Furthermore, both FH subjects with and without elevated Lp(a) had higher plasma levels of AA compared with controls ( P < 0·001). The multivariable analyses showed associations between dietary n -6 FA intake and plasma levels of AA ( P = 0·02) and between plasma levels of Lp(a) and AA ( P = 0·006). Our data suggest a novel link between plasma Lp(a) concentration, dietary n -6 FA and plasma AA concentration, which may explain the small diet-induced increase in Lp(a) levels associated with lifestyle changes. Although the increase may not be clinically relevant, this association may be mechanistically interesting in understanding more of the role and regulation of Lp(a).